2022
DOI: 10.1111/vec.13191
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of cardiopulmonary arrest and resuscitation in hospitalized birds: 41 cases (2006–2019)

Abstract: ObjectiveTo describe circumstances and outcomes following cardiopulmonary arrest (CPA) in hospitalized birds.DesignRetrospective case study.SettingAcademic medical center.MethodsThe hospital medical records system was searched for avian cases that underwent CPR. Medical records were reviewed; data retrieved included association of CPA with anesthesia or handling, use of external compressions and intubation, drug administration, rates of return of spontaneous circulation (ROSC), and outcome. Cases with incomple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…7 The effectiveness of CPR in birds is unknown, but small retrospective studies have shown promise, with up to 7% of birds undergoing CPR showing successful return of spontaneous circulation (ROSC). 8,9 The primary aim of the current study was to evaluate the effect of 3 different cardiac compression techniques, SC, SC with interposed caudal coelomic compressions (ICCC), and lateral compressions (LC), on directly measured arterial pressures and gross postmortem findings after compressions. [10][11][12] Because CPR research is uncommonly performed in chickens, additional information was also collected that could serve for future experimental studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The effectiveness of CPR in birds is unknown, but small retrospective studies have shown promise, with up to 7% of birds undergoing CPR showing successful return of spontaneous circulation (ROSC). 8,9 The primary aim of the current study was to evaluate the effect of 3 different cardiac compression techniques, SC, SC with interposed caudal coelomic compressions (ICCC), and lateral compressions (LC), on directly measured arterial pressures and gross postmortem findings after compressions. [10][11][12] Because CPR research is uncommonly performed in chickens, additional information was also collected that could serve for future experimental studies.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively fixed, dorsal position and rigid parenchyma of the lungs, as opposed to expansile and contractile mammalian lungs, may also somewhat limit the efficacy of the thoracic pump 7 . The effectiveness of CPR in birds is unknown, but small retrospective studies have shown promise, with up to 7% of birds undergoing CPR showing successful return of spontaneous circulation (ROSC) 8,9 …”
Section: Introductionmentioning
confidence: 99%